Modulating release of ranibizumab and aflibercept from thiolated chitosan-based hydrogels for potential treatment of ocular neovascularization - Moreno, Miguel (2017)
Background: This paper describes the synthesis of thiolated chitosan-based hydrogels with varying degrees of crosslinking that has been utilized to modulate release kinetics of two clinically relevant FDA-approved anti-VEGF protein drugs, ranibizumab and aflibercept. These hydrogels have been fabricated into disc shaped structures for potential use as patches on ocular surface.